Vom System zum Netzwerk Medien, Politik und Journalismus in Kurdistan - Schamberger, Kerem (Westend Verlag, 2022)
In his clear and detailed study, Schamberger illuminates a largely unknown side of Kurdistan by turning his gaze to the Kurdish media landscape: It turns out that a transnational Kurdish media network exists in the Middle East that extends all the way to Europe. This network is part of the self-organisation and resistance of Kurds against their expulsion and assimilation. It is resolutely against the status quo, wants to transform society and at the same time criticises the supposedly universal principles of Western journalism. Kurdish media are inherently militant because they are a product of rebellion against oppression from the very beginning. This is precisely why lessons can be drawn from their practice for other political and social movements whose aim is to build media beyond the capitalist mainstream and to change society in an emancipatory sense.